Effect of Modified Carbon Nanotubes Epoxy on the Mechanical Properties of Concrete Reinforced with FRP Sheets - Kazemi, Hamid; Heydari, Mostafa; Bamoharam, Fateme Farash (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Today, using Fiber Reinforced Polymer (FRP) sheets is one of the conventional methods in retrofitting concrete structures. Some factors affecting FRP sheets proper performance include mechanical properties, surface specifications, connector`s material and connecting approach in concrete elements. Previous studies showed that FRP epoxy resin and its basic surface have a significant impact on the ultimate bearing capacity.
Keywords: carbon nanotube; epoxy resin; fibre reinforced polymer; mechanical properties; reinforce concrete; FRP sheet; mechanical testing; nanorurka węglowa; żywica epoksydowa; kompozyt; właściwości mechaniczne; beton zbrojony; mata FRP